Implementation of an Adaptive Method for Changing the Frequency Division of the Counter Clock Signal in a Frequency-to-Code Converter - Dariusz Świsulski; Piotr Warda (Energies, 2023)
Processing physical quantities into an indirect signal is a standard method of transferring information about the measured quantity to the master system, which analyzes the data obtained from the acquisition system. The intermediate signal is very often the voltage, but another transmission medium can be the frequency of the output signal of the “physical quantity-to-frequency” converter. The article presents the implementation of the adaptive method of selecting the clock signal frequency of the counter working in the converter. The issue of selecting the clock signal frequency for the required processing range of the transducer is discussed in detail. The application of the method using the STM32L476RG microcontroller is presented. The principle of checking the processing range of the developed transducer model is discussed. The algorithms of transducer operation in basic and adaptive modes of measuring the period of the variable frequency signal are proposed. The results of operation, in both modes, of the transducer model of frequency processing are presented, along with the metrological analysis of the results. The influence of selected approximations used to reconstruct the measured quantity on the final presentation of the measurement result is discussed.